Manajemen Kas dalam Ekonomi Islam: Studi Kasus pada Bank Syariah di Indonesia - Kharidatul Hasanah; Faidatus Syiriah; Siti Zakia Khalidah Ma`ruf; Falda Nabila Fauziyah; Mukhlishotul Jannah (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
Cash management is one of the most crucial aspects of financial management in a company, serving to maintain liquidity, optimize fund utilization, and ensure smooth operations. This study aims to analyze effective strategies and techniques in cash management to improve financial efficiency in a business entity. The method used is a literature review with a qualitative descriptive approach. The results show that proper cash management through cash flow planning, expenditure control, and the utilization of cash surpluses can help companies avoid liquidity issues and increase profitability. Therefore, efficient cash management is essential to support the long-term stability and growth of a company.